2016
DOI: 10.1186/s12887-016-0643-5
|View full text |Cite|
|
Sign up to set email alerts
|

Health, schooling, needs, perspectives and aspirations of HIV infected and affected children in Botswana: a cross-sectional survey

Abstract: BackgroundAntiretroviral treatment means many HIV infected children are surviving with a highly stigmatised condition. There is a paucity of data to inform policies for this growing cohort. Hence we carried out a study on the health, schooling, needs, aspirations, perspectives and knowledge of HIV infected and affected children in Botswana.MethodsA cross-sectional survey using interviews and focus group discussions among HIV infected children aged 6–8 years versus HIV aged matched HIV uninfected counterparts l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 5 publications
4
34
1
Order By: Relevance
“…It is expected that most children living with HIV in Malawi and other sub-Saharan countries will in time achieve an average lifespan, similar to that achieved today in high-income countries [ 36 ]. It is critically important that children living with HIV know that they have the disease and that they are able to manage it properly so they maximise their own health and wellbeing and minimise the threat they pose to others [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that most children living with HIV in Malawi and other sub-Saharan countries will in time achieve an average lifespan, similar to that achieved today in high-income countries [ 36 ]. It is critically important that children living with HIV know that they have the disease and that they are able to manage it properly so they maximise their own health and wellbeing and minimise the threat they pose to others [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the TEEWA survey, school attendance was high, above 85%, for both ALPHIV and controls, in the upper range compared to other studies in various age groups (8)(9)(10)(11)(12)14). However, among adolescents living in family settings, school attendance was lower among ALPHIV than among general population controls (83% vs. 94%, respectively).…”
Section: Discussionmentioning
confidence: 56%
“…In a recent study in South Africa, Fotso et al found that HIV-infection significantly reduced adolescent school attainment and that contextual factors could only explain 18% of the attainment gap (8). While neurocognitive impairments connected to HIV-infection can directly impact academic achievements, school absenteeism for frequent illness or HIV-related stigmatization could mediate the negative effect of HIV-infection on school life (6,11,12,14). In the TEEWA survey, about 20% of ALPHIV mentioned episodes or extended periods of school absenteeism for medical reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, women and girls are the majority of the HIV‐affected population (UNWOMEN, ); therefore, they are more likely to suffer from the effects of this disease. Intergenerational (parent‐to‐child) transmission of education in case of HIV/AIDS: Children with HIV/AIDS‐ill parents may observe that their parents physically deteriorate from the disease and may experience both parents’ deaths, sometimes in quick succession. This may lead to posttraumatic stress syndrome, depression, poverty, and stigma (Cluver et al ., ; Anabwani et al ., ; UNAIDS, ). To the extent that children's educational attainment is highly correlated with parental education (Becker and Tomes, ; Björklund and Salvanes, ), HIV may interfere with intergenerational (parent‐to‐child) transmission of human capital.…”
Section: Introductionmentioning
confidence: 99%